Successful Treatment of Narcolepsy and Cataplexy: A Review - B Lockrane; P Bhatia; Robin Gore (Canadian Respiratory Journal)
A 25-year-old woman with narcolepsy and cataplexy was treated with well-recognized drugs for these conditions. Because she did not respond, a decision was made to treat her with sodium oxybate.